Evaluation of Regional Taste Function in Healthy Thai Subjects Using Standard Suprathreshold Tastants: - Phonmanee, Tharatham; Sastranuruk, Naruphon; Assanasen, Paraya; Atipas, Kawita (Siriraj Medical Journal, 2025)
Objective: To evaluate regional taste function in normal Thai subjects using standard suprathreshold tastants. Materials and Methods: A total of 93 healthy Thai subjects (41 males and 52 females), aged 20 to 60 years, were recruited. Regional taste function was assessed using four standard suprathreshold tastants, with both identification scores and VAS scores recorded. Results: The mean total taste identification score was 10.7 on the right side and 10.8 on the left side, with no statistically significant differences between sides across all subgroups. The mean VAS score was highest for sweet tastants and for the posterior tongue as the tested area. No significant differences were observed between sexes or among age groups when analyzed by tastant and area. Conclusion: The regional (spatial) taste test is a useful gustatory test. This study establishes normative values for Thai subjects, which can be used in future clinical practice for patient evaluations.